Design heat exchanger network by graph method - Huu Tung, Nguyen (Vietnam Journal of Science and Technology, 2017)
The  problem  of  synthesizing  a  network  of  heat  exchangers  can  be  resolved  by  the temperature – enthalpy diagram or by the table method, but they are not convenient in large heat exchanger network design.  In  this  study, we use graph  theory  to present  and  to design  a heat exchanger  network.  This method  is  one way  to  avoid  the  difficulties  inherent with  applying temperature – enthalpy diagram or table method to a large complex network and the presentation of network as a grid in graph theory is very clear and allows for easy modification